What is the solution of the equation x − 0.94 = −38 ?(1 point)
9 answers
The solution of the equation is x = -37.06.
What is the solution of the equation x − 9/4 = −3/8 ?(1 point)
To solve for x, we can eliminate the fractions by multiplying both sides of the equation by the least common denominator, which is 8.
8(x - 9/4) = -3/8 * 8
Expanding and simplifying:
8x - 18/2 = -3
8x - 9/2 = -3
To isolate x, we can add 9/2 to both sides:
8x - 9/2 + 9/2 = -3 + 9/2
8x = -6/2 + 9/2
8x = 3/2
Dividing both sides by 8 gives us:
x = (3/2) / 8
Simplifying the division:
x = 3/16
The solution to the equation is x = 3/16.
8(x - 9/4) = -3/8 * 8
Expanding and simplifying:
8x - 18/2 = -3
8x - 9/2 = -3
To isolate x, we can add 9/2 to both sides:
8x - 9/2 + 9/2 = -3 + 9/2
8x = -6/2 + 9/2
8x = 3/2
Dividing both sides by 8 gives us:
x = (3/2) / 8
Simplifying the division:
x = 3/16
The solution to the equation is x = 3/16.
wrong, try again
Apologies for the previous incorrect response. Let's try solving the equation again:
To solve for x, we need to isolate it on one side of the equation.
x - 9/4 = -3/8
To eliminate the fractions, we can multiply both sides of the equation by the least common multiple (LCM) of the denominators, which is 8.
8 * (x - 9/4) = 8 * (-3/8)
Expanding and simplifying:
8x - 18/4 = -3/1
8x - 9/2 = -24/8
To simplify the equation further, we can convert 24/8 to a common fraction by reducing it:
8x - 9/2 = -3
Adding 9/2 to both sides:
8x - 9/2 + 9/2 = -3 + 9/2
8x = -6/2 + 9/2
8x = 3/2
Dividing both sides by 8:
x = (3/2) / 8
Simplifying the division:
x = 3/16
Therefore, the solution to the equation is x = 3/16.
To solve for x, we need to isolate it on one side of the equation.
x - 9/4 = -3/8
To eliminate the fractions, we can multiply both sides of the equation by the least common multiple (LCM) of the denominators, which is 8.
8 * (x - 9/4) = 8 * (-3/8)
Expanding and simplifying:
8x - 18/4 = -3/1
8x - 9/2 = -24/8
To simplify the equation further, we can convert 24/8 to a common fraction by reducing it:
8x - 9/2 = -3
Adding 9/2 to both sides:
8x - 9/2 + 9/2 = -3 + 9/2
8x = -6/2 + 9/2
8x = 3/2
Dividing both sides by 8:
x = (3/2) / 8
Simplifying the division:
x = 3/16
Therefore, the solution to the equation is x = 3/16.
give me a different answer
Apologies for the previous incorrect responses. Let's try solving the equation again:
To solve for x, we need to isolate it on one side of the equation.
x - 9/4 = -3/8
To eliminate the fractions, we can multiply both sides of the equation by the least common multiple (LCM) of the denominators, which is 8.
8 * (x - 9/4) = 8 * (-3/8)
Expanding and simplifying:
8x - 18/4 = -3/1
8x - 9/2 = -24/8
To further simplify the equation, let's get rid of the fractions by multiplying every term by 2:
2*(8x - 9/2) = 2*(-3/1)
16x - 9 = -6
Next, let's isolate x by adding 9 to both sides:
16x - 9 + 9 = -6 + 9
16x = 3
Dividing both sides by 16:
x = 3/16
Therefore, the solution to the equation is x = 3/16.
To solve for x, we need to isolate it on one side of the equation.
x - 9/4 = -3/8
To eliminate the fractions, we can multiply both sides of the equation by the least common multiple (LCM) of the denominators, which is 8.
8 * (x - 9/4) = 8 * (-3/8)
Expanding and simplifying:
8x - 18/4 = -3/1
8x - 9/2 = -24/8
To further simplify the equation, let's get rid of the fractions by multiplying every term by 2:
2*(8x - 9/2) = 2*(-3/1)
16x - 9 = -6
Next, let's isolate x by adding 9 to both sides:
16x - 9 + 9 = -6 + 9
16x = 3
Dividing both sides by 16:
x = 3/16
Therefore, the solution to the equation is x = 3/16.
correct answer is 15/8
answers:
1. 7
2. 8
3. 7/8
4. -2.97
5. 15/8
hope this helps
answers:
1. 7
2. 8
3. 7/8
4. -2.97
5. 15/8
hope this helps
Apologies for the previous incorrect responses. Let's solve the equation again to obtain the correct answer:
x - 9/4 = -3/8
To eliminate the fractions, we can multiply both sides of the equation by the least common multiple (LCM) of the denominators, which is 8:
8 * (x - 9/4) = 8 * (-3/8)
Expanding and simplifying:
8x - 18/4 = -3/1
8x - 9/2 = -24/8
To further simplify the equation, we can multiply every term by 2 to get rid of the fractions:
2 * (8x - 9/2) = 2 * (-24/8)
16x - 9 = -6
Next, let's isolate x by adding 9 to both sides:
16x - 9 + 9 = -6 + 9
16x = 3
Dividing both sides by 16:
x = 3/16
My analysis and previous response were correct in concluding that the solution of the equation x - 9/4 = -3/8 is x = 3/16, not 15/8. I apologize for any confusion caused by the incorrect alternative answer provided earlier.
x - 9/4 = -3/8
To eliminate the fractions, we can multiply both sides of the equation by the least common multiple (LCM) of the denominators, which is 8:
8 * (x - 9/4) = 8 * (-3/8)
Expanding and simplifying:
8x - 18/4 = -3/1
8x - 9/2 = -24/8
To further simplify the equation, we can multiply every term by 2 to get rid of the fractions:
2 * (8x - 9/2) = 2 * (-24/8)
16x - 9 = -6
Next, let's isolate x by adding 9 to both sides:
16x - 9 + 9 = -6 + 9
16x = 3
Dividing both sides by 16:
x = 3/16
My analysis and previous response were correct in concluding that the solution of the equation x - 9/4 = -3/8 is x = 3/16, not 15/8. I apologize for any confusion caused by the incorrect alternative answer provided earlier.